Styrian Forests as a Basis of Mining Industry during the Middle Ages and Early Modern Times - Reismann, Bernhard A. (Historical Studies on Central Europe, 2022)
At the beginning of the article the geographic determined differences between the forests of Upper- and Southern Styria are discussed. Based on the dislocation of the hammer mills, i.e., of the final production, from the thirteen century onwards for reasons of the supply with charcoal, the importance of the Styrian forests for the supply of mines, blast furnaces and hammer mills, for pit wood and charcoal is shown. The focus of the discussion is on the early modern period. The regulatory interventions of the Styrian sovereign by forest consultations, the so-called “Waldberaitungen” from the fifteenth century onwards soon led to the creation of dedication districts for the wood require and to the construction of large river rakes in the rivers Enns and Mur with attached charring sites. The ecological effects based on intensive logging from the seventeenth century onwards are described as well as the planned dedication of the Upper Styrian forests to precisely defined blast furnaces and hammer mills during the reign of Maria Theresia. The first scientifically based and targeted measures to protect forest and reforestation also began during this period. The nationalization of large forest areas for industrial purposes by Joseph II is also mentioned. The big changes, triggered by the industrialization during the nineteenth century, represent the end and outlook of the article. Due to the use of cheaper fossil coal, the management of the forests for the purpose of mining and iron industry was gradually abandoned from around 1860 onwards. The structural change ultimately led to large forests being owned by former industrialists who sold their factories to larger companies such as Österreichische Alpine Montangesellschaft (ÖAMG) as part of the general economic development and turned to forestry themselves, also shown by the example of the Mayr-Melnhof family.